Paroxysmal Laryngospasm: A Rare Condition That Respiratory Physicians Must Distinguish from Other Diseases with a Chief Complaint of Dyspnea - Yu Bai; Xi-Rui Jing; Yun Xia; Xiao-Nan Tao (Canadian Respiratory Journal)
Background. In recent years, we have observed respiratory difficulty manifested as paroxysmal laryngospasm in a few outpatients, most of whom were first encountered in a respiratory clinic. We therefore explored how to identify and address paroxysmal laryngospasm from the perspective of respiratory physicians. Methods. The symptoms, characteristics, auxiliary examination results, treatment, and prognosis of 12 patients with paroxysmal laryngospasm treated in our hospital from June 2017 to October 2019 were analyzed. Results. Five males (42%) and 7 females (58%) were among the 12 Han patients sampled. The average age of the patients was 49.25 ± 13.02 years. The disease course ranged from 14 days to 8 years and was characterized by sudden dyspnea, an inability to inhale and exhale, a sense of asphyxia, and voice loss during an attack. Eight patients with gastroesophageal reflux were cured after antacid treatment. One case of upper respiratory tract infection (URI) was completely relieved after symptomatic treatment. One patient with left vocal cord paralysis experienced complete relief after specialist treatment by an otorhinolaryngologist. Episodes in 1 patient were significantly reduced after lifestyle improvement. One patient experienced spontaneous relief after rejecting treatment. Conclusions. Paroxysmal laryngospasm is a rare laryngeal disease that generally occurs secondary to gastroesophageal reflux disease (GERD), and antireflux therapy is frequently effective for its treatment. A respiratory physician should master and identify the symptoms and differentiate this condition from hysterical stridor, reflux-related laryngospasm, and asthma. Timely referral to otolaryngologists, gastroenterologists, and other specialists for standardized examination and regular treatment should be provided when necessary.